OPTICAL ADD DROP MULTIPLEXERS (OADMS) IN UW-WDM OPTICAL PASSIVE COMMUNICATION NETWORKS - Mohammed, Abd El-Naser A.; Rashed, Ahmed Nabih Zaki; Eid, Mahmoud M.A. (International Journal of Computing, 2010)
In the present paper, we have been modeled numerically and parametrically the high and best performance functions of optical add drop multiplexers (OADMs) for ultra wide wavelength division multiplexing technique with ultra wide space division multiplexing technique in advanced optical communication networks and photonic networking over the assumed set of parameters. Moreover, we have analyzed and investigated the maximum time division multiplexing (MTDM) and soliton transmission techniques to be processed to handle bit rate either per link or per channel for cables of multi-links (20-120 links/core). Where maximum number of transmitted channels in the range of 1000-4800 channels are processed to handle the product of bit rate either per channel or per link for cables of multilinks of silica cable core fabrication material. The MTDM or soliton transmission bit rates either per link or per channel are also treated over wide range of the affecting parameters under the ambient temperature variations. Also, the performance characteristics of the OADMs are taken as the major interest in optical networks to handle maximum transmission bit rates for the supported subscribers.